Vitamin D Status and Its Influence on the Health of Preschool Children in Hangzhou - Zhaojun Chen; Xi Lv; Wensheng Hu; Xia Qian; Ting Wu; Yunxia Zhu (Frontiers Media S.A., 2021)
Objective: Vitamin D deficiency and insufficiency in children are global public health problems. However, few studies have focused on vitamin D status in healthy preschool children, especially in Asia. This study aimed to investigate vitamin D status and host-related factors in healthy preschool children in Hangzhou to analyze the impact of low vitamin D levels (<30 ng/mL) on health outcomes (obesity, early childhood caries, and respiratory tract infections).Methods: A total of 1,510 healthy children aged 24-72 months from 15 kindergartens in Hangzhou were included. Data on the children's gender, age, body mass index (BMI), caries, and blood samples available for vitamin D analysis were collected from June to August 2018. A total of 325 children aged 36-48 months took part in a survey on the frequency of respiratory tract infections in the last year.Results: The children's mean 25(OH)D level was 28.01 ± 7.29 ng/mL. A total of 11.4% of the children had vitamin D deficiency, and 52.6% had vitamin D insufficiency. Only 36.0% had vitamin D sufficiency. No significant difference was found by gender or BMI group. However, children in the obesity group had the highest prevalence of vitamin D deficiency and the lowest 25(OH)D levels. A significant negative correlation was found between the 25(OH)D level and child age (r = −0.144, p < 0.001). Regression analysis showed that the children's 25(OH)D levels decreased by 0.17 ng/mL per month with age. In addition, children with low vitamin D levels might increase the risk of obesity and early childhood caries. Multiple linear regression indicated that the number of caries in children increased by 0.08 per 1-ng/mL decrease in the 25(OH)D level (β = −0.08, p < 0.001).Conclusion: Vitamin D deficiency/insufficiency is a serious problem among healthy preschool children in Hangzhou. Public health policies or interventions should be implemented to ensure that preschool children have adequate vitamin D to reduce the risk of related diseases.